VISUALISASI POTRET ANAK JALANAN KOTA SEMARANG MELALUI FILM DOKUMENTER - Anthony Y.M. Tumimomor; Yohanes Rio Ferdinan (Institut Bisnis dan Teknologi Indonesia, 2019)
The Semarang city is one of the cities with a high population of street childrens in Central Java, based on data in 2017, there are approximately 300 street childrens scattered in various spots in the Semarang city. Factors causing the descline of children to the streets are exploitation from parents, the economy, the environment and the encouragement of friends, so that it requires special attention from all parties, the role of the community to know the background of street children so that later they can be involved in efforts to alleviate them. Considering the importance of delivering this information, Then a documentary film designed for street children portraits that can comprehensively describe the reality or facts of street children. This research applies a mixed method and linear strategy in the process of problem identification, analysis, data collection and media design. The results of the visualization of portraits of street children by using this documentary film, are able to provide information in reality of the life and activities of street children to the people of Semarang City in particular and Indonesian society in general.